Building and cultivating business to government guanxi in China and its potential challenges from western firm's perspective - Yi, Wang (My University, 2010)
China’s increased assertion and its huge potential market demands more attention to be given to the unique aspects of conducting business in China. One of the unique aspects which has been significantly concerned is the practice of guanxi. The main purpose of the present study is to explore how to build and cultivate business to government (B2G) guanxi in China (PRC) and explore its potential challenges from western firm’s perspective. In order to achieve the main purpose of the study, three objectives are discussed. The first objective is to analyze the phenomenon of guanxi in order to increase basic understanding of guanxi. The Second objective is to explore the building stages and the main cultivating strategies of B2G guanxi in China. The last objective is to empirically explore how a Finnish firm has tried to develop its B2G guanxi in China and explore the potential challenges. Transaction cost theory, social capital, and in-group identification are the theoretical approach. The present study follows a deductive research approach and qualitative research method. The data is mainly collected from two face-to-face interviews and one interview guided questionnaire. In addition, annual report of the case company is used as another source of evidence. The main findings are the following: in China, B2G guanxi is built through four consecutive stages: targeting, scouting, signaling, and packaging. Targeting refers to identify the officials with whom the western firm wants to build its B2G guanxi. Scouting has to do either by group identification or altercasting so as to close the gap between western firm and identified officials. At Signaling stage, western B2G guanxi seekers should deliver appropriate signals to the target officials in the context of a broader social event. At packaging stage, westerners should carefully hide their instrumental objectives unless their B2G gaunxi is further improved. Practicing social interactions, holding informal discussions, gift-giving, and building trust are the main cultivating strategies to improve B2G guanxi. Lack of Chinese language proficiency, different communication styles, and unclearness of communicating and having close B2G guanxi with the officials are the main potential challenges to western firms.
Keywords: Guanxi; business to government guanxi; building stages; cultivating strategies; challenges.; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|